International group working to identify Russian forces that carried out grisly war crimes on Kherson prisoners - Macias, Amanda (CNBC, 2023)
According to new evidence gathered by the investigation, at least 36 victims described the use of electrocution during interrogations of Kherson prisoners.
Keywords: 2023-08 August; Kherson; Russian Army; Russian Federation; War Crimes